Pengaruh Metode Mastery Learning Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Fikih - Nursyafika; Ritonga, Supardi (Universitas Majalengka, 2023)
This research aims to determine the implementation of the mastery learning method in the class VIII fiqh subject at MTs Annahdhatud Diniyah Pangkalan Batang Barat and to determine the effect of the mastery learning method on student learning outcomes in the class VIII fiqh subject at MTs Annahdhatud Diniyah Pangkalan Batang Barat. The method used in this research is a quantitative method with a quasi-experimental approach and how tests and documentation work. The total population of this study was the entire class VIII consisting of 39 students and used as 2 class samples. In analyzing the data in this research, researchers used the paired sample t-test. The results of the paired sample test using the SPSS version 25 program obtained a Sig value. (2-tailed) of 0.000 < 0.05. Thus, there is a significant influence of the mastery learning method on student learning outcomes in class VIII jurisprudence subjects at MTs Annahdhatud Diniyah Pangkalan Batang Barat.